Abnormal red cell structure and function in neuroacanthocytosis. - Judith C A Cluitmans; Carlo Tomelleri; Zuhal Yapici; Sip Dinkla; Petra Bovee-Geurts; Venkatachalam Chokkalingam; Lucia De Franceschi; Roland Brock; Giel J G C M Bosman (PLoS ONE)
Background Panthothenate kinase-associated neurodegeneration (PKAN) belongs to a group of hereditary neurodegenerative disorders known as neuroacanthocytosis (NA). This genetically heterogeneous group of diseases is characterized by degeneration of neurons in the basal ganglia and by the presence of deformed red blood cells with thorny protrusions, acanthocytes, in the circulation. Objective The goal of our study is to elucidate the molecular mechanisms underlying this aberrant red cell morphology and the corresponding functional consequences. This could shed light on the etiology of the neurodegeneration. Methods We performed a qualitative and semi-quantitative morphological, immunofluorescent, biochemical and functional analysis of the red cells of several patients with PKAN and, for the first time, of the red cells of their family members. Results We show that the blood of patients with PKAN contains not only variable numbers of acanthocytes, but also a wide range of other misshapen red cells. Immunofluorescent and immunoblot analyses suggest an altered membrane organization, rather than quantitative changes in protein expression. Strikingly, these changes are not limited to the red blood cells of PKAN patients, but are also present in the red cells of heterozygous carriers without neurological problems. Furthermore, changes are not only present in acanthocytes, but also in other red cells, including discocytes. The patients' cells, however, are more fragile, as observed in a spleen-mimicking device. Conclusion These morphological, molecular and functional characteristics of red cells in patients with PKAN and their family members offer new tools for diagnosis and present a window into the pathophysiology of neuroacanthocytosis.